Recurrent hyperparathyroidism due to parathyroid and pulmonary tumors showing features of parathyroid adenoma - Miyauchi, Ryosuke (Radiol Case Rep, 2020)
We report on a case of recurrent primary hyperparathyroidism possibly caused by parathyroid adenocarcinoma metastasizing to the lung. A 46-year-old woman with a history of parathyroid adenoma, which was extirpated 8 years ago, presented with symptoms of primary hyperparathyroidism, and was found to have a parathyroid and a lung nodule in radiographic assessments. Resections of the tumors in the parathyroid gland as well as the lung were required to improve her condition, and in pathology, both tumors demonstrated benign features consistent with adenoma. However, from the perspective of the clinical course and location of the tumors, we deduced that the tumors were malignant despite being identified as benign by conventional pathological examination. The integration of information based on clinical status and imaging studies is essential to evaluate the malignant potential of tumors if a patient with hyperparathyroidism has tumors located both inside and outside of the parathyroid gland.